PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGARUHNYA PADA KINERJA INDIVIDUAL PADA BANK PERKREDITAN RAKYAT DI KABUPATEN TABANAN - SAGUNG RAI DARMINI, ANAK AGUNG; WIJANA ASMARA PUTRA, I NYOMAN (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
This research aims to investigate factors influencing the utilization of information technology (IT), like social factor, affect factor, job appropriateness, long-term consequences, facilitating condition, and job complexity; as well as the impact of utilization and trust on IT on individual performance of People Credit Bank (Bank Perkreditan Rakyat/BPR) in Tabanan Regency. Sample consists of 13 BPR with total respondents of 96. Data collection method is interview, survey with questionnaire, and documentation. Instruments used in this research have met validity and reliability criteria and pass multicolinearity and heteroscedasticity tests. Data then are analyzed using multiple linear regression tests. Based on the analysis, it is found that social factor and the facilitating condition give positive impacts and significantly support the utilization of IT. Affect factor, job appropriateness, and long-term consequences provide positive impacts, yet not significant; while complexity factor has negative and insignificant impact on the utilization of IT. As a whole, all factors affect IT utilization positively and significantly. Utilization and trust on IT each has positive and significant impact on individual performance; and together they also affect individual performance positively and significantly.
Keywords: information technology, individual performance, social factor, affect factor, job appropriateness